PENINGKATAN KAPASITAS KEWIRAUSAHAAN SEBAGAI UPAYA PELESTARIAN KULINER TEMPO DULU DESA PIJI KABUPATEN KUDUS - Rini, Gilang Puspita; Septanti, Annisya Lutfi; Khoeron, Slamet (Universitas Mataram, 2025)
Micro, Small and Medium Enterprises (MSMEs) have proven to be able to overcome the wave of the Covid-19 pandemic. Resilience to the impact of the crisis occurred because of the entrepreneurial capabilities possessed by MSMEs, especially at the home industry level. However, these small businesses are not free from problems. The problem that occurs is the lack of understanding of increasing management capacity, including production management and marketing management. Therefore, the community service team from Universitas Muria Kudus assisted Roti Global to improve its entrepreneurial capabilities through various training and implementation of machine technology that helps the production process. Roti Global is located in Piji Village, Dawe District, Kudus Regency. The methods used were Focus Group Discussion (FGD), socialization of improving the production process, marketing training, application of technology and observation and impact analysis. In the end, the goal of the Universitas Muria Kudus team's community service was achieved